Protective effector memory CD4 T cells depend on ICOS for survival. - Tamson V Moore; Bryan S Clay; Caroline M Ferreira; Jesse W Williams; Magdalena Rogozinska; Judy L Cannon; Rebecca A Shilling; Amanda L Marzo; Anne I Sperling (PLoS ONE, 2011)
Memory CD4 T cells play a vital role in protection against re-infection by pathogens as diverse as helminthes or influenza viruses. Inducible costimulator (ICOS) is highly expressed on memory CD4 T cells and has been shown to augment proliferation and survival of activated CD4 T cells. However, the role of ICOS costimulation on the development and maintenance of memory CD4 T cells remains controversial. Herein, we describe a significant defect in the number of effector memory (EM) phenotype cells in ICOS(-/-) and ICOSL(-/-) mice that becomes progressively more dramatic as the mice age. This decrease was not due to a defect in the homeostatic proliferation of EM phenotype CD4 T cells in ICOS(-/-) or ICOSL(-/-) mice. To determine whether ICOS regulated the development or survival of EM CD4 T cells, we utilized an adoptive transfer model. We found no defect in development of EM CD4 T cells, but long-term survival of ICOS(-/-) EM CD4 T cells was significantly compromised compared to wild-type cells. The defect in survival was specific to EM cells as the central memory (CM) ICOS(-/-) CD4 T cells persisted as well as wild type cells. To determine the physiological consequences of a specific defect in EM CD4 T cells, wild-type and ICOS(-/-) mice were infected with influenza virus. ICOS(-/-) mice developed significantly fewer influenza-specific EM CD4 T cells and were more susceptible to re-infection than wild-type mice. Collectively, our findings demonstrate a role for ICOS costimulation in the maintenance of EM but not CM CD4 T cells.